Personality traits as mediators in the association between SIRT1 rs12415800 polymorphism and depressive symptoms among Chinese college students - Wang, Chenliu; Ji, Lei; Ren, Decheng; Yuan, Fan; Liu, Liangjie; Bi, Yan; Guo, Zhenming; Yang, Fengping; Xu, Yifeng; Yu, Shunying; Yi, Zhenghui; He, Lin; et al. (Frontiers in Psychiatry, 2023)
Abstract Background: Previous research has linked polymorphisms in the SIRT1 gene to depressive symptoms, particularly in Chinese individuals. However, it is not clear how personality traits may contribute to this association. Methods: To explore the potential mediating effect of personality traits, we utilized a mediation model to examine the relationship between the SIRT1 rs12415800 polymorphism and depressive symptoms in 787 Chinese college students. Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression (CES-D) scale, while personality traits were measured using the Big Five Inventory (BFI). Results: Our analysis indicated a significant association between the SIRT1 rs12415800 polymorphism and depressive symptoms, with this relationship partially mediated by the personality traits of neuroticism and conscientiousness. Specifically, individuals who were heterozygous for the rs12415800 polymorphism and had higher levels of conscientiousness were less likely to experience depressive symptoms. Conversely, those who were homozygous for the rs12415800 polymorphism and had higher levels of neuroticism were more likely to experience depressive symptoms. Conclusions: Our results suggest that personality traits, particularly neuroticism and conscientiousness, may play a critical role in the association between the SIRT1 rs12415800 polymorphism and depressive symptoms among Chinese college students. These findings highlight the importance of considering both genetic factors and personality traits when exploring the etiology of depressive symptoms in this population.